2022
DOI: 10.31348/2022/10
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Practices in Cataract Surgery- Subjective Preferences of Czech Cataract Surgeons

Abstract: Aims: The aim of the work was to find out the current subjective preferences of Czech cataract surgeons in terms of individual procedures, techniques and materials used during cataract surgery. Material and methods: This study was conducted in the form of a questionnaire (online, a total of 44 questions). The survey respondents were members of the Czech Society of Refractive and Cataract Surgery. Questions 1–10 concerned the characteristics of the respondent (age, number of operations performed, type of workp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…A similar survey of the ASCRS membership showed increasing adoption rates from 30% in 2007 to 50% in 2014 and 66% in 2021. [ 20 21 ] A recent survey of Czech cataract surgeons showed that 98% used intracameral antibiotics,[ 22 ] whereas a recent Turkish study reported 89% usage. [ 23 ] Slightly older studies from Italy (50% adoption in 2016), the UK (45% in 2010), China (33% in 2019), and Japan (7% adoption in 2014) show lower rates of use.…”
Section: Discussionmentioning
confidence: 99%
“…A similar survey of the ASCRS membership showed increasing adoption rates from 30% in 2007 to 50% in 2014 and 66% in 2021. [ 20 21 ] A recent survey of Czech cataract surgeons showed that 98% used intracameral antibiotics,[ 22 ] whereas a recent Turkish study reported 89% usage. [ 23 ] Slightly older studies from Italy (50% adoption in 2016), the UK (45% in 2010), China (33% in 2019), and Japan (7% adoption in 2014) show lower rates of use.…”
Section: Discussionmentioning
confidence: 99%